Place (and Such Things) - Fortis, Massimo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2013)
In “Place, Production and Scenography: international theory and practice since 1962,” the conclu ding chapter of Kenneth Frampton’s Modern Architecture: A Critical History, published in London in 1980, the author gives an account of recent architectural developments and trends in progress at the time of the writing. Having underlined the ineffectiveness of operative planning in the development of the physical form of settlements, toward which he seemed to show a certain indifference, he examined the potential promise of urban design, noting: «There is, as Hans Sedlmayr has pointed out, a moment when place and production are fused together to yield that quality of character from which we receive our identity.» This fundamental issue raised in the brief introduction points to the division between architectural culture and architectural practice, between a line of action oriented toward interpreting the dominant methods of production and a second, more defensive one, which aims to re-establish the sense of relations, while running the risk of slipping into the introversion of the enclave. The con- sequence is a loss of the very sense of “urbanness” and, ultimately, quality of life. Nor does it seem possible for an incentive to come from the population itself, which seeks a remedy for its discomfort mostly by turning to the reassuring visage of tradition, if not to its post-modern parody, failing to go «beyond the surface issue of style to demand that architectural practice should re-address itself to the issue of place creation, to a critical yet creative redefinition of the concrete qualities of the built domain.»